Out of the Ashes: Ecological Resilience to Extreme Wildfire, Prescribed Burns, and Indigenous Burning in Ecosystems - Eisenberg, Cristina; Anderson, Christopher L.; Collingwood, Adam; Sissons, Robert; Dunn, Christopher J.; Meigs, Garrett W.; Hibbs, Dave E.; Murphy, Scott; Kuiper, Sierra Dakin; SpearChief-Morris, Julian; Little Bear, Leroy; Johnston, Barb; et al. (Frontiers in Ecology and Evolution, 2019)
Until Euro-American colonization, Indigenous people used fire to modify eco-cultural systems, developing robust Traditional Ecological Knowledge (TEK). Since 1980, wildfire activity has increased due to fire-suppression and climate change. In 2017, in Waterton Lakes National Park, AB, the Kenow wildfire burned 19,303 ha, exhibiting extreme fire behavior. It affected forests and the Eskerine Complex, a native-grass prairie treated with prescribed burns since 2006 to reduce aspen (Populus tremuloides) encroachment linked to fire suppression and bison (Bison bison bison) extirpation. One-year post-fire, the Kenow wildfire caused vigorous aspen sprouting, altered stand structure to an early-seral state, and dominant land cover from grass to mineral soil. It did not change aspen-cover extent, or cause non-native grass eruption, but reduced native-grass diversity, and produced more pronounced shifts in ecosystem structure and biodiversity than the prescribed burns. The 2017 Kenow wildfire and prescribed burns differed in phenological timing, scale, and severity. Prescribed burns occurred in late spring, with little fuel available, while the Kenow wildfire occurred in late summer, with abundant fuel—amplifying the difference in severity. As in other climate-limited fire regimes, prescribed burns treatments did not mitigate the severity of the Kenow wildfire. To more effectively reduce the extent of aspen cover, future prescribed burns in this system could be applied in the late season. Incorporating TEK in adaptive co-management can help create more resilient ecosystems for fire and pervasive stressors such as invasive plants, provided one contextualizes current conditions and how they differ from historical conditions.